2018
DOI: 10.1007/s13595-018-0694-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for growth and wood chemical properties in Eucalyptus urophylla × E. tereticornis hybrids

Abstract: & Key message Growth and wood chemical properties are important pulpwood traits. Their narrow-sense heritability ranged from 0.03 to 0.49 in Eucalyptus urophylla × E. tereticornis hybrids, indicating low to moderate levels of genetic control. Genetic correlations were mostly favorable for simultaneous improvement on growth and wood traits. Additive and non-additive genetic effects should be considered in making a hybrid breeding strategy. & Context Eucalypt hybrids are widely planted for pulpwood production pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
4
12
0
Order By: Relevance
“…Fine percent had higher SCA estimation and mean curl had smaller GCA estimation (Table 7). SCA estimation for fibre length was relatively higher Estimates of specific combining ability are given for the top 10 values Estimates of heritability for fibre traits were low to medium for fibre percent (0.01) and fibre width (0.19), which were in general agreement with the eucalypt hybrids studied by Zhu et al (2017) (0.04) and Chen et al (2018) (0.06-0.49). Heritability of fibre width was higher than that of fibre length, indicating more genetic gain could be obtained from fibre width by genetic improvement as previously found by Wu et al (2011).…”
Section: Estimation Of Gca and Scasupporting
confidence: 56%
See 2 more Smart Citations
“…Fine percent had higher SCA estimation and mean curl had smaller GCA estimation (Table 7). SCA estimation for fibre length was relatively higher Estimates of specific combining ability are given for the top 10 values Estimates of heritability for fibre traits were low to medium for fibre percent (0.01) and fibre width (0.19), which were in general agreement with the eucalypt hybrids studied by Zhu et al (2017) (0.04) and Chen et al (2018) (0.06-0.49). Heritability of fibre width was higher than that of fibre length, indicating more genetic gain could be obtained from fibre width by genetic improvement as previously found by Wu et al (2011).…”
Section: Estimation Of Gca and Scasupporting
confidence: 56%
“…High genetic correlation value between growth traits and wood properties had been widely described in Eucalyptus and other species (Kien et al 2009, Kube et al 2001, Wu et al 2011, Chen et al 2018. High genetic correlation indicates that the expression of both traits is most likely controlled by the same class of genes in an organism (Chen et al 2018).…”
Section: Genetic Correlation Between Traitsmentioning
confidence: 93%
See 1 more Smart Citation
“…grandis [26] and E . urophylla [2729]. Recently, a comprehensive study has developed global NIRS models using wood samples from different tropical, subtropical, and temperate eucalypt species grown in different locations around the world, but unfortunately no samples of urograndis hybrids were included [30].…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating E. urophylla x E. tereticornis hybrid performance at 10 years of age, Chen et al (2018) observed environmental coefficients of variation from 30 to 43% for DBH and from 23 to 30% for height. Evaluating trees at several ages, Li et al (2017) observed values of environmental coefficients from 11.7 to 23.7% for height, 13.5 to 26.6% for DBH, and 31.6 to 53.8% for wood volume in E. cloesiana progenies.…”
Section: Resultsmentioning
confidence: 99%